Fundamental study of the integrated process of heavy oil pyrolysis and coke gasification. Part Ⅰ: Effect of CO and H2 in syngas atmosphere on heavy oil pyrolysis. (15th September 2022) - Xiong, Qing-an; Zhang, Yuming; Huang, Youjian; Li, Jiazhou; Zhang, Wei
Highlights: Effect of CO and H2 in syngas atmosphere on heavy oil pyrolysis are studied. CO and H2 could inhibit the decomposition of liquid products. CO and H2 could reduce the coke condensation degree to increase its reactivity. Abstract: An integrated process of heavy oil pyrolysis and coke gasification was proposed to realize the in-situ gasification of coke and provide syngas (CO/H2 ) atmosphere for heavy oil pyrolysis to obtain high-quality liquid products. To reveal the reaction mechanism of syngas (CO/H2 ) on heavy oil pyrolysis, the pyrolysis characterizations of three heavy oils including Dagang slurry oil (DG-SO), Qingdao vacuum residue (QD-VR) and Canadian oil-sands bitumen (CA-OB) were evaluated at different atmospheres (N2, CO, CO/H2, and H2 ). The results showed that compared with QD-VR and CA-OB, DG-SO with high content of aromatics but high Conradson carbon residue (CCR) value was not suitable for the integrated process of heavy oil pyrolysis and coke gasification. Compared with the N2 atmosphere, the pyrolysis oil yields of DG-SO, QD-VR, and CA-OB increased in turn under CO, CO/H2, and H2 atmospheres. On the contrary, their coke and gas yields decreased in turn. Furthermore, the contents of CH4, C2 -C5, and CO2 in pyrolysis gases all decreased in turn, while the contents of their alkane, olefin, aromatic hydrocarbon, and oxygen /nitrogen/sulfur compounds in pyrolysis oil increased in turn. The change of oil and gas composition indicated that compared with N2, both CO and H2 could inhibit further decomposition of liquid products. The reactivity of coke showed that CO and H2 could reduce the degree of condensation of coke to increase its reactivity, but the effect of CO was not as good as that of H2 .